Considerations in the selection of patient-reported outcome measures for assessing function related to chronic ankle instability - Luan, Lijiang; Witchalls, Jeremy; Newman, Phil; Pranata, Adrian; Ganderton, Charlotte; Tirosh, Oren; El-Ansary, Doa; Adams, Roger David; Waddington, Gordon; Han, Jia (Frontiers in Bioengineering and Biotechnology, 2025)
Patient-reported outcome measures (PROMs) are essential tools in evaluating chronic ankle instability (CAI), capturing subjective experiences such as “giving way” and instability. However, no standardized guidelines exist for selecting PROMs in CAI, resulting in limited comparability across studies and clinical settings. This paper highlights four key considerations for selecting PROMs in assessing CAI: recalibration in populations including individuals with CAI, identifiability of ankle instability, detectability of CAI characteristics, and cross-cultural adaptability. It emphasizes that CAI-specific PROMs should demonstrate high pertinence, accurately distinguishing CAI from other conditions, and effectively detecting symptom changes over time. Furthermore, widely adopted PROMs may offer greater credibility and applicability. Addressing these considerations is crucial for improving CAI diagnosis, treatment evaluation, and advancing patient-centered care.